Pengaruh Pendidikan dan Pelatihan terhadap Peningkatan Produktivitas Kerja Karyawan-Karyawati PT Panasonic Gobel Indonesia Jakarta Timur - Bakti Toni Endaryono; Ace Jaja Juansah; Nizmah Nizmah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
The purpose of this study was to determine the effect of education and training on the improvement of work productivity of employees of PT Panasonic Gobel Indonesia, East Jakarta. The independent variables used in this study are education and training. While the dependent variable used is the increase in employee productivity. The object used in the research is PT Panasonic Gobel Indonesia, with employees of the customer service division as the research sample. A total of 30 respondents. The research method with quantitative, data collection techniques with interviews, observation and documentation, the analysis used is simple linear regression analysis. From the results of the regression coefficient analysis linear function Y = 13.633 + 0.682. The results showed that education and training had a significant positive effect on the increase in work productivity of female employees, amounting to 71%.